Gender and Language Proficiency Interaction on Language Learning Strategies of ESL Learners - Ho, Ai Ping; Ng, Lee Luan (Jurnal Komunikasi: Malaysian Journal of Communication, 2025)
Employing language learning strategies will lead to greater language communication ability and academic achievement. Even though studies on language learning strategies have been conducted over the years, it is still crucial to look at individual factors affecting the choice of language learning strategies used among the learners. Gender and language proficiency of learners are two prominent variables influencing the use of language learning strategies in learning English as a second language (ESL). Thus, this study aims to identify the interaction effects between gender and language proficiency of 1699 first-year undergraduates in utilising language learning strategies in learning the English language through a self-reported survey using an adapted version of the Strategy Inventory for Language Learning (SILL) (Oxford, 1990) in a Malaysian public university. Findings revealed that the ESL learners were found to use the language learning strategies in an average manner irrespective of their gender and language proficiency. Data analysis through two-way ANOVA revealed a significant interaction between gender and learner’s language proficiency in utilising effective strategies. The differential effects of these two independent variables on affective strategies were further investigated through their simple effects and Tukey’s HSD tests. These tests revealed that female average achievers differed significantly in employing effective strategies compared to male average achievers. This study implied that investigating the employment of language learning strategies in various contexts is worthwhile, as well as incorporating mixed method research for richer data.